Effect of the Theory-driven Educational Intervention on Self-Care Behavior and Glycosylated Hemoglobin Level in Patients with Type 2 Diabetes - Pourmohammad, Mojgan; Maheri, Mina; Khalkhali, Hamid Reza; Moghaddam-Tabrizi, Fatemeh; Didarloo, Alireza (Current Diabetes Reviews, 2024)
Background and Aims: The diabetics' lack of knowledge about self-care and incorrect beliefs in this care are the reasons for their admission to hospitals. The present study aimed to examine the impact of education based on the theory of planned behavior (TPB) on intention, self-care behavior, and glycosylated hemoglobin (HbA1c) levels in patients with Type 2 Diabetes. Methods: The present study was conducted on 60 diabetic patients who were randomly classified into intervention and control groups. In the intervention group, self-care education based on TPB was held, but the control group only received routine care. The data were collected using a fourpart questionnaire including characteristics, items of patients’ knowledge, items of TPB constructs, and items of diabetes self-care. Data were analyzed in SPSS software. Results: In intervention group, mean score of self-care behavior and its domains significantly changed from (total: 52.26±14.75, diabetic diet: 22.20±6.05, exercise: 5.17±4.04, blood sugar testing: 5.03 ± 4.15, medication: 5.40±2.28, foot care: 13.47±8.42) into 76.66±8.87, 29.43±5.48, 7.60±2.60, 8.73±2.31, 6.48±1.09, 23.53±3.09, respectively three months after intervention (p<0.01). In this case, these changes were not seen in the control group. The mean level of HbA1c in the intervention group (6.38±0.16) was significantly lower than before the intervention (7.56±1.08) and the control group (8.02±0.25) three months after intervention (p<0.01). Conclusion: Education based on the TPB was effective in improving the patients' self-care behavior and HbA1c index. Therefore, we suggest all medical centers to use the TPB as an effective and low-cost educational approach to improve diabetics' self-care behavior and health.
Keywords: self-care behavior